Perbandingan Kebijakan Hukum Terhadap Perkawinan Anak dari Perspektif Hukum Perkawinan di Indonesia dan Malaysia - Utami, Dwi; Hidayah, Astika Nurul (Jurnal Hukum In Concreto, 2024)
Problems related to child marriage occur due to several educational, economic, cultural, and environmental factors. This has more negative impacts than positive impacts, not only a serious problem in Indonesia but also in neighboring countries such as Malaysia. Therefore, this study aims to analyze the comparison of legal policies in Indonesia and Malaysia against child marriage. This research method is normative juridical by a examining legislative documents, books, journals, and other literature studies related to this research. The results show that the age limit for marriage in Indonesia is 19 years for men and women, while in Malaysia the age limit for marriage for men is 18 years and 16 years for women. The policy applied in Indonesia to prevent child marriage is to raise the age limit of marriage and fulfill PERMA Number 5 of 2019, while in Malaysia, if a child marriage is to take place, it must fulfill the Standard Operating Procedure of the Sharie Judge and the policy applied to prevent child marriage through 'urf which is formed through the level of education, economy, and psychology.  Keywords: child marriage, marriage age limit, policy